Trends in Marketing Capabilities - Silvia L. Martin (Revista CEA, 2021)
Contemporary companies focus on marketing because of its importance and commercial advantages. Nevertheless, this also means they should face significant challenges and other organizations in this field. Firms require organizational structural factors to identify customer needs, consumer engagement, and market sensing. This is achieved through product exploration and exploitation, which increases the stock supply of SMEs for new and existing customers along with their profits. The adoption of electronic commerce has become essential for SMEs, especially in the IT sector, because it enables them to analyze several metrics, improve customer service, and reduce operating costs. In addition, they can be more efficient in distribution and customer communication. Thus, service promotes customer loyalty and improves confidence. New product development increases profits and creates opportunities to fulfill market needs. E-commerce opens new markets, supports customer service, and improves communication.  In summary, these three marketing capabilities are useful to gain competitive advantages in the long term and develop a differentiating factor against direct competition.